2014
DOI: 10.1128/aem.02114-14
|View full text |Cite
|
Sign up to set email alerts
|

The Intimin-Like Protein FdeC Is Regulated by H-NS and Temperature in Enterohemorrhagic Escherichia coli

Abstract: c Enterohemorrhagic Escherichia coli (EHEC) is a Shiga-toxigenic pathogen capable of inducing severe forms of enteritis (e.g., hemorrhagic colitis) and extraintestinal sequelae (e.g., hemolytic-uremic syndrome). The molecular basis of colonization of human and animal hosts by EHEC is not yet completely understood, and an improved understanding of EHEC mucosal adherence may lead to the development of interventions that could disrupt host colonization. FdeC, also referred to by its IHE3034 locus tag ECOK1_0290, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The Ve subclass of AT proteins are referred to as IATs, due to their similarity with classical monomeric AT proteins, but with the passenger and translocation domain in opposite locations within the primary amino acid sequence. Two well-studied proteins from this subclass include intimin and FdeC of E. coli , both of which have been extensively characterised 48 . Here, we characterised the YeeJ IAT protein from K-12 strain MG1655; we performed an in silico analysis of the yeeJ gene, determined the prevalence of yeeJ , and demonstrated that it is surface localized and mediates biofilm formation in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ve subclass of AT proteins are referred to as IATs, due to their similarity with classical monomeric AT proteins, but with the passenger and translocation domain in opposite locations within the primary amino acid sequence. Two well-studied proteins from this subclass include intimin and FdeC of E. coli , both of which have been extensively characterised 48 . Here, we characterised the YeeJ IAT protein from K-12 strain MG1655; we performed an in silico analysis of the yeeJ gene, determined the prevalence of yeeJ , and demonstrated that it is surface localized and mediates biofilm formation in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysates, OMVs extractions and bacterial concentrated supernatants were subjected to SDS-PAGE and were transferred to PVDF microporous membrane filters as previously described 48 . Culture supernatants were prepared by filtering (pore size 0.22 μm) to remove intact bacterial cells and concentrated 100× by size exclusion centrifugal filtration.…”
Section: Methodsmentioning
confidence: 99%
“…From analysis by protein crystallography and structural modeling, FdeC carries 10 Big domains, and is predicted to extend substantially from the outer surface of the outer membrane ( Nesta et al 2012 ). FdeC provides adhesive properties important in two modes of attachment for E. coli : bacteria displaying FdeC on their surface are better able to interact with each other to form biofilms ( Easton et al 2014 ), and FdeC on ExPEC was shown to bind specifically to collagen and to promote colonization of kidney tissue surfaces ( Easton et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the assembly pathway for the expression of both the classic intimin (EaeA) and what now appears to be the typical representative of the family, FdeC, reveal an involvement of the TAM as a common feature in both cases. FdeC was recently shown to function as an adhesin in ExPEC ( Nesta et al 2012 ; Easton et al 2014 ). While the majority of the sequences in the grouping are most similar to FdeC, a further and widespread group appears instead to be two-partner secretion systems using the inverse autotransporter as the delivery device.…”
Section: Introductionmentioning
confidence: 99%
“…These adherence systems reflect the ability of commensal 10.1601/nm.3093 to colonize distinct niches during its transit through the different compartments of the bovine gastro-intestinal tract. It is also of interest to note that some of these adherence systems possess characteristics corresponding to physiological conditions encountered in the bovine gastro-intestinal tract: i) eaeH expression is induced at 39 °C, the internal bovine temperature, but not at 37 °C [ 38 ] ii) the pili HCP is involved in adherence of 10.1601/nm.3093 to bovine gut explants [ 39 ] and iii) the F9 fimbriae are essential for in vivo colonization of calves [ 40 ]. Furthermore, the stg and F9 gene clusters are strongly associated with 10.1601/nm.3093 belonging to phylogenetic group B1 [ 41 , 42 ].…”
Section: Genome Propertiesmentioning
confidence: 99%